2010
DOI: 10.1002/dvg.20620
|View full text |Cite
|
Sign up to set email alerts
|

Ehd4 is required to attain normal prepubertal testis size but dispensable for fertility in male mice

Abstract: The four highly homologous members of the C-terminal EH domain-containing (EHD) protein family (EHD1-4) regulates endocytic recycling. To delineate the role of EHD4 in normal physiology and development, mice with a conditional knockout of the Ehd4 gene were generated. PCR of genomic DNA and Western blotting of organ lysates from Ehd4 −/− mice confirmed EHD4 deletion. Ehd4 −/− mice were viable and born at expected Mendelian ratios; however, males showed a 50% reduction in testis weight, obvious from postnatal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…1C). Similar phenotypes, such as small testes but normal fertility or sperm count, have been reported in mice with targeted deletions of gene members from the C-terminal EH domain-containing (EHD) protein family (EHD4)45, the Pumilio gene family (Pum2)46, the protein inhibitor of activated STAT (PIASx) family47, and the cytochrome c family48. In addition, other mouse models with gene cluster deletions, such as deletions of the Dickkopf (DKK) family49, the testicular haploid expressed gene (Theg) family50, and the ADP-ribosylation factor (ARF) family51, have shown that specific gene members are dispensable for development or fertility.…”
Section: Discussionsupporting
confidence: 56%
“…1C). Similar phenotypes, such as small testes but normal fertility or sperm count, have been reported in mice with targeted deletions of gene members from the C-terminal EH domain-containing (EHD) protein family (EHD4)45, the Pumilio gene family (Pum2)46, the protein inhibitor of activated STAT (PIASx) family47, and the cytochrome c family48. In addition, other mouse models with gene cluster deletions, such as deletions of the Dickkopf (DKK) family49, the testicular haploid expressed gene (Theg) family50, and the ADP-ribosylation factor (ARF) family51, have shown that specific gene members are dispensable for development or fertility.…”
Section: Discussionsupporting
confidence: 56%
“…Consistent with these findings, a recent study demonstrated involvement of EHD3 in EE-to-Golgi retrograde transport aberrant Golgi morphology, function, and delayed biosynthetic transport of lysosomal enzymes [29]. On the other hand, the modest phenotypes described for EHD1 knock-down mice [30, 31] suggest that with 86% identity to EHD1, EHD3 may be highly functionally redundant with EHD1 in most tissues. Ultimately, the generation of double knock-out mice will be key to determining the degree of EHD1/EHD3 functional redundancy.…”
Section: Ehd3mentioning
confidence: 56%
“…More recently, an additional EHD1 mouse model demonstrated that EHD1 expression is required for normal spermatogenesis and fertility of male mice [32], consistent with the fly phenotype. It is noteworthy that loss of the EHD1 paralogue and oligomerisation partner, EHD4, is not necessary for male mouse fertility, but is needed to allow testis development to normal size [31]. Plants such as Arabidopsis thaliana also have homologues of EHD proteins (AtEHD1 and At EHD2), [65], and studies point to a role for these proteins in regulating endocytosis and signaling [66, 67].…”
Section: Introductionmentioning
confidence: 99%
“…We have found that EHD1 deletion on a mixed C57BL/6 and 129Sv background is partially penetrant embryonic lethal and associated with defective spermatogenesis and lens developmental defects, while it is fully embryonic lethal on a predominantly C57BL/6 background [3537]. Here, we use primary bone marrow-derived macrophages (BMDMs) with inducible EHD1-Knockout (EHD1-KO) capacity, to study the biological and physiological function of EHD1 in macrophages.…”
Section: Introductionmentioning
confidence: 99%